Selective thrombolysis trans-catheter for safe and effective subacute stent graft occlusion treatment - Hung Nguyen Duc, MD; Lam Truong Hoai, MD; Long Nguyen Tuan, MD; Minh Tran Duc, MD; Linh Duong Cong, MD (Radiology Case Reports, 2023)
A 74-year-old man developed a subacute thrombosis with a stent graft occlusion, 4 months after an endovascular aneurysm repair. He presented with lateral lower limb ischemia and presented intermittent claudication. Using an intra-arterial thrombolysis transcatheter infusion and angioplasty. We report successful endovascular and medical treatment. The patient recovered without complications and was discharged.